The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012 IEEE Conference on Visual Analytics Science and Technology (VAST) 2012
DOI: 10.1109/vast.2012.6400492
|View full text |Cite
|
Sign up to set email alerts
|

Inter-active learning of ad-hoc classifiers for video visual analytics

Abstract: Learning of classifiers to be used as filters within the analytical reasoning process leads to new and aggravates existing challenges. Such classifiers are typically trained ad-hoc, with tight time constraints that affect the amount and the quality of annotation data and, thus, also the users' trust in the classifier trained. We approach the challenges of ad-hoc training by interactive learning, which extends active learning by integrating human experts' background knowledge to greater extent. In contrast to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 35 publications
(45 reference statements)
1
61
0
Order By: Relevance
“…Heimerl et al [40] proposed to tightly integrate the user into the labelling process and suggested an interactive binary classifier training approach for text analysis. Höferlin et al [41] presented a system to build cascades of linear classifiers for image classification.…”
Section: Visual Classificationmentioning
confidence: 99%
“…Heimerl et al [40] proposed to tightly integrate the user into the labelling process and suggested an interactive binary classifier training approach for text analysis. Höferlin et al [41] presented a system to build cascades of linear classifiers for image classification.…”
Section: Visual Classificationmentioning
confidence: 99%
“…One of the first systems doing so is the Informedia system which employs speech and video analysis in conjunction with effective user interfaces [7]. A system targeting computer vision algorithm developers is presented in [16] allowing the user to gain insight in features and how to use these features in surveillance. Canopy [3] is an advanced system combining text analysis, various visualizations, and visual similarity based matching to explore visual collections.…”
Section: A Multimedia Visualization and Analyticsmentioning
confidence: 99%
“…Finally, an inter-active learning system [16] provides feedback on classification quality to users by means of a set of integrated cascaded scatter plots of the instances class distribution, in each stage of the classifier. Annotated instances are also organized by their similarity, using a tdistributed stochastic neighbor embedding (tSNE) [47].…”
Section: Visual Data Classificationmentioning
confidence: 99%